PROGNOSTIC SIGNIFICANCE OF CT-PLANIMETRIC CHARACTERISTICS OF THE PANCREAS IN THE DEVELOPMENT OF PANCREATIC FISTULA AFTER PANCREATODUODENECTOMY - Usenko, Olexander; Symonov, Oleh; Pavliuk, Romanna; Vasyliuk, Serhii; Tkachuk, Oleh (Eastern Ukrainian Medical Journal, 2025)
Introduction. The study investigates the prognostic significance of preoperative computed tomography (CT) parameters, particularly pancreatic parenchymal density and duct-to-parenchyma (D/P) ratio, in predicting the risk of postoperative pancreatic fistula (POPF) following pancreatoduodenectomy (PD). POPF remains a major postoperative complication, with incidences between 6–60%, prolonging hospital stays and escalating treatment costs. This research addresses the limitations of subjective intraoperative assessments, proposing objective, preoperative CT-based criteria to forecast POPF risk. Methods. A prospective study was conducted with 234 patients undergoing PD between January 2022 and November 2023. The research employed multiphase contrast-enhanced CT imaging to assess pancreatic density (in Hounsfield Units, HU) and D/P ratio at the expected resection site above the superior mesenteric vein. Density was measured using unenhanced CT, while D/P ratios were calculated based on duct and parenchymal measurements in two planes. The radiologists were blinded to patient outcomes, and logistic regression models were utilized to assess the prognostic value of these metrics. Results. The study identified a significant association between lower pancreatic density and increased POPF risk. Patients with POPF had a median density of 22 HU compared to 39.65 HU in patients without POPF. Similarly, lower ventrodorsal and craniocaudal D/P ratios correlated with higher POPF incidence. Logistic regression models demonstrated that low pancreatic density and D/P ratio are independent predictors of POPF, with an area under the ROC curve (AUC) of 0.91 for pancreatic density and 0.86 for the D/P ratio. A combined model achieved the highest prognostic accuracy (AUC = 0.92), suggesting these parameters are valuable for preoperative POPF risk stratification. Conclusions The study concludes that low pancreatic density and a low D/P ratio, identified through preoperative CT planimetry, are reliable predictors of POPF following PD. These parameters enable a more objective risk assessment, potentially guiding individualized surgical strategies to mitigate POPF risk. Future studies with larger cohorts are warranted to validate these findings and explore histological correlations.